(untitled) (International Journal of Engineering Sciences & Management Research, 2017)
In this work, a parametric study of the technology and economic imperatives for stranded natural gas processing was carried out, the economic analysis was done using a template developed on Microsoft Excel to calculate the cash flows, evaluate the Net Present Values (NPV), and obtain the Internal Rate of Return/Discounted Cash flow Rate of Return (IRR/DCFRR) which are key economic indices for ranking of projects. Discounted Cash Flow economic model is preferred here for the validation of the stranded natural gas concept select because it is the only economic system that takes into account variations in inflation, tax rate and other parameters. To validate my model, parameters from the Escravos GTL Plant and the proposed Nigeria LNG Train 7 plant were used. The template provided values for these economic indices (NPV and IRR) for the plants under various scenarios when the values of key input economic parameters were varied. The impact of variation of the following economic parameters on the NPV and IRR were assessed: the plant capital expenditure (CAPEX), the discount rate, the tax rate, the plant operating expenditure (OPEX), the feed gas cost, the crude oil price, the LNG price, and the product shipping cost. An economic sensitivity analysis of the plants was also carried out using Tornado charts. To provide a basis for proper economic comparison, the capacities of both plants were scaled up to obtain their CAPEX if they were both processing 1500 MMSCFD using standard cost-capacity relationships. The results obtained at the base case scenario using the most likely values of the economic input parameters, indicate that the NLNG T7 has a CAPEX of 11.77 billion, NPV of 0.89 billion, and IRR of 11.45% while the EGTL has a CAPEX of 23.15 billion, NPV of -7.34 billion, and IRR of 2.51%. This implies that the NLNG T7 is more viable than the EGTL because of its lower CAPEX, higher NPV and higher IRR at the base case scenario values. The analysis also indicated that for the EGTL to be profitable, the crude oil price has to be at least 85/barrel or the interest on capital lower than 2.51%. The results from the sensitivity analysis show that the profitability of the EGTL is most affected by the plant CAPEX followed by the crude oil price, while the profitability of the NLNG T7 is most affected by LNG price followed by the plant CAPEX. From the results obtained, the LNG option is more viable than GTL option for gas monetisation in Nigeria .